An Assessment Of The Performance Of The Different Types Of Biomass (Agricultural) Waste When Used As Fuels In A Gasifier Stove. - Waniala, Benedictor; Nassimbwa , Florence (Student's Journal of Health Research Africa, 2021)
Introduction: The world is experiencing adverse climatic changes due to the high demand for biomass energy with an increasing population. Many forests are being cut down to meet the biomass energy demand. A lot of research to identify alternative fuels especially from agricultural waste is being tried. Pinewood, pine cones, maize cobs, and wood shavings are among the fuels that are regarded as a waste but can be used in a gasifier stove as alternative fuels amidst the depleting forests. Methodology: The study was conducted from the Biomass Resource and Training Center of Nyabyeya Forestry College located in Masindi near Budongo Forest, Uganda. From the results, Wood shavings had the lowest specific fuel consumption of 90g/liter as compared to pine wood with 101g/liter, maize cobs with 103g/liter, and pine cones with the highest of 107g/liter. Results: maize cobs were found to be a better alternative fuel for the gasifier stove use, this is because their time to boil 2.5 liters of water is about 12 minutes, the burning rate is 20g/min, the specific fuel consumption was about 104g/liter and had the best thermal efficiency of about 33% with the specific gasifier stove. Recommendation: Maize cobs are recommended for use in the gasifier stoves, apart from the scientific evidence, maize cobs have other benefits associated with their wide availability and cheap or no cost since they exist as agricultural wastes, this would help in reducing the pressure on forests for wood fuels like charcoal and firewood. Conclusion: Pine cones had the lowest time to boil of 9.5 minutes compared to maize cobs with 12.25 minutes and pinewood with the highest which was 13.25 minutes.